Proteinograma De LÍQuido sinovial E anÁlise histopatolÓgica das articulaÇÕes metacarpofalangeanas de muar com osteoartrite desencadeada por deformidade flexural - Daneze, Edmilson Rodrigo [UNESP]; Fachini, Vinicius; De Melo Cardoso, Juniocesar Donizete; Maia, Ricardo Silva; De Faria, Jonatas Ferreira; De Toledo, Carmen Zilda Pereira [UNESP]; Da Rosa Sobreira, Márcia Ferreira [UNESP] (My University, 2015)
The flexural deformities are characterized by permanent hyperflexion of one or more joint areas, consequently, the bad shaping overload the structures that form the joints triggering arthritis or osteoarthritis. This aims to report a case of bilateral tendon contracture of the metacarpophalangeal joint in a mule who did not respond to conservative treatment. The radiographic exam visualized signs consistent with osteoarthritis, being more intense in the metacarpophalangeal joint left. After bilateral tenotomy the deep digital flexor tendon it was found contracture correction, but there was no regression of the local inflammatory process, deciding euthanasia. In histopathological examination of the joint tissues were observed loss of cartilage architecture and large areas of fibrosis in both joints, while there was also the left cell hypertrophy and hyperplasia of the synovial membrane and slight infiltration of neutrophils. Samples of synovial fluid showed adequate viscosity, reddish coloration and slight turbidity; protein concentrations in the liquid observed high concentrations of á1-acid glycoprotein, ceruloplasmin and IgA IgG on both sides, while the concentrations of total proteins, albumin and haptoglobin were increased only in the left hip. We can conclude that the 15 day intervals for animal care associated with constant and repetitive friction of the metacarpophalangeal joints during locomotion, due to flexor deformity, caused an intense inflammatory process in place that led to osteoarthritis in the left joint and arthritis in the right joint.
Proteinogram of liquid synovial and histopathological analysis of metacarpophalangeal joints of the hinny with osteoarthritis triggered by flexor deformity
Keywords: Arthritis; Electrophoresis; Flexural deformity; Histopathology; Tenotomy